A unique case report revealing the elusive clinical phenomenon of meningitis retention syndrome - Sajal Gupta; Kishan Raj K; Prashanth Adiga K (Urology Case Reports)
Meningitis retention syndrome (MRS) represents a rare condition in which there is meningitis accompanied by urinary retention in the absence of any other neurological symptoms. MRS is usually misdiagnosed as a urinary tract infection due to varied clinical symptoms. It is a self-limiting syndrome that often presents with prodromal symptoms of meningitis. We report a case of MRS in a 26-year-old Indian male who presented clinically with features of meningitis and developed urinary retention during hospitalisation. Fewer than 30 cases have been described and several of them remain undiagnosed due to lack of diagnostic criteria. Any patient with fever and headache which are prodromal symptoms of meningitis followed by retention should be evaluated for MRS.